If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ((3x + 8)(x + 8)) = 2ln(x + 8) Reorder the terms: ((8 + 3x)(x + 8)) = 2ln(x + 8) Reorder the terms: ((8 + 3x)(8 + x)) = 2ln(x + 8) Multiply (8 + 3x) * (8 + x) ((8(8 + x) + 3x * (8 + x))) = 2ln(x + 8) (((8 * 8 + x * 8) + 3x * (8 + x))) = 2ln(x + 8) (((64 + 8x) + 3x * (8 + x))) = 2ln(x + 8) ((64 + 8x + (8 * 3x + x * 3x))) = 2ln(x + 8) ((64 + 8x + (24x + 3x2))) = 2ln(x + 8) Combine like terms: 8x + 24x = 32x ((64 + 32x + 3x2)) = 2ln(x + 8) (64 + 32x + 3x2) = 2ln(x + 8) Remove parenthesis around (64 + 32x + 3x2) 64 + 32x + 3x2 = 2ln(x + 8) Reorder the terms: 64 + 32x + 3x2 = 2ln(8 + x) 64 + 32x + 3x2 = (8 * 2ln + x * 2ln) 64 + 32x + 3x2 = (16ln + 2lnx) Solving 64 + 32x + 3x2 = 16ln + 2lnx Solving for variable 'x'. Reorder the terms: 64 + -16ln + -2lnx + 32x + 3x2 = 16ln + 2lnx + -16ln + -2lnx Reorder the terms: 64 + -16ln + -2lnx + 32x + 3x2 = 16ln + -16ln + 2lnx + -2lnx Combine like terms: 16ln + -16ln = 0 64 + -16ln + -2lnx + 32x + 3x2 = 0 + 2lnx + -2lnx 64 + -16ln + -2lnx + 32x + 3x2 = 2lnx + -2lnx Combine like terms: 2lnx + -2lnx = 0 64 + -16ln + -2lnx + 32x + 3x2 = 0 The solution to this equation could not be determined.
| 1/5(a-15)=10 | | -2+6/-2 | | -(7y+2)-(-6y-5)=3 | | 2/3k-(k-1/2)=1/6(k-51) | | 0.23y-0.8=0.13y+1-0.8y | | 4/-2 | | 3m-13=-1+7m | | x=-2/12-5/12 | | 3/8u=24 | | .5x^2-40x+408=0 | | (p+3)+(4p-9)/r | | 6(4x-8)= | | z+9.8=3.1 | | (p+3)/r+(4p-9)/r | | .3x^2-11.1x+85.8=0 | | 3x^2-11.1x+85.8=0 | | 24=7y+4 | | -(4x+2)-6(x+3)=4-(7x+1) | | -(7y+5)-(6y-6)=-4 | | 5x=(3x-2)(m+7) | | x+2/1=-9/1 | | 5x+14=6x+2 | | 5x-4x=1 | | x^4-3x^2+2x=0 | | (7/5)/(7/20) | | r/-1=-3 | | 6x+2+3x+15=180 | | 4=-2(4.5p+2.5) | | p=2(16)+2(80) | | 5x^2/x=4x+1 | | 5x^2+x^2=0 | | 7.36=2*3.14*r |